Application of Xylanolitic Fungi Inoculum of Aspergillus Tubingensis R. Mossery in Bamboo (Bambusa Sp.) Litter Composting. Issue 1 (January 2021) - Irawan, B; Putri, L F; Farisi, S; Suratman,
Abstract: Bamboo is a plant that is easily found in various regions in Indonesia. Bamboo leaves are abundant and usually difficult to decompose naturally, so they are usually only burned. In fact, bamboo leaves can be a good source of organic material if processed properly. One way that can be used to overcome these problems is composting. The purpose of this study was to determine the effect of Aspergillus tubingensis (xylanolytic Fungi) inoculum with corn medium on the bamboo litter composting process. This research was conducted in a Completely Randomized Design (CRD) with 4 treatments consisting of Control (bamboo litter only), T1 (bamboo litter + 1% inoculum), T2 (bamboo litter + 1.5% inoculum), and T3 (bamboo litter + 2% inoculum) with 3 replications in each treatment. Chemical analysis is carried out at the 4th, 8th, and 12th weeks of composting. The result indicates that application of xylanolytic fungi inoculum of A. tubingensis gives dynamic results to C, N, P, and C / N ratio of bamboo litter compost during weeks 4, 8 and 12.